Distribution and abundance of Pale-bellied Brent Geese and Wigeon on Strangford Lough, Northern Ireland - Mathers, R.G.; Portig, Alexander; Montgomery, Ian (1998)
Strangford Lough, County Down holds internationally important numbers of wintering Pale-bellied Brent Geese Branta bernicla hrota with peak counts of up to 16 000. In the past, the Lough was also important for overwintering Wigeon Anas penelope with peak counts up to 20 000 in the early 1970s. However, this population has declined drastically with winter peaks at fewer than 2000 since the mid-1980s. As the overall flyway numbers of Wigeon have not fallen over this period, it has been suggested that the reasons for the decline are intrinsic to Strangford Lough. Wigeon did not decline uniformly throughout Strangford Lough. The greatest fall in numbers occurred on the northern mudflats suggesting a decline in carrying capacity. Factors responsible for this decline may include the reduction of Eelgrass Zostera spp. which is the main food of both species, and increases in human activity near and on the foreshore, especially in the case of Wigeon. Indirect interspecific interactions between Brent Geese and Wigeon are discussed as they may have been significant in reducing the numbers of Wigeon in the system.